Electronic structure calculation of vanadium‐and scandium‐based endohedral fullerenes VSc2N@C2n (2n = 70, 76, 78, 80). Issue 24 (28th September 2018) - Bhusal, Shusil; Baruah, Tunna; Yamamoto, Yoh; Zope, Rajendra R.
Abstract: We present candidate structures for the most stable isomers for the VSc2 N@C70, VSc2 N@C76, VSc2 N@C78, and VSc2 N@C80 using a systematic procedure that involves all possible isomers of the host fullerene cages. Subsequently, a detailed investigation of structural and electronic properties of the lowest energy isomers is performed using density functional theory in combination with large polarized Gaussian basis sets. The search correctly identifies the experimentally observed VSc2 N@C80 isomer as the most stable structure. The structural analysis shows that only VSc2 N@C70 has a non‐IPR cage among the four endohedral fullerenes. Respectively, VSc2 N@C70 and VSc2 N@C76 have nearly degenerate spin states with total spin S = 0 and S = 1. All the lowest energy cages are energetically stable and show significant electron accepting capacity comparable to C60 . Abstract : Endohedral fullerenes containing transition metal clusters offer possibility to tweak the magnetic and electronic properties of these fullerenes. Here we predict the most stable isomers of VSc2 N@C2 n (where 2n = 70, 76, 78, 80) by performing a very elaborate search which include all known isomers of the host fullerene cages.